Pulse pressure and prognosis in patients with heart failure with reduced ejection fraction. (28th March 2019) - Shah, Neeraj; Qian, Min; Di Tullio, Marco R.; Graham, Susan; Mann, Douglas L.; Sacco, Ralph L.; Lip, Gregory Y. H.; Labovitz, Arthur J.; Ponikowski, Piotr; Lok, Dirk J.; Anker, Stefan D.; Teerlink, John R.; et al.
Abstract: Background: A high pulse pressure (PP) is associated with adverse cardiovascular (CV) outcomes; however, this relationship may be reversed in patients with heart failure with reduced ejection fraction (HFREF). Methods: Patients from the WARCEF trial with left ventricular ejection fraction ≤35% were included. PP was divided into tertiles: ≤42, 42‐54 and >54 mm Hg. Age and ejection fraction adjusted Kaplan‐Meier curves were generated to evaluate the relationship between PP and outcomes [mortality, CV mortality, stroke and HF hospitalizations (HFH)]. Cox proportional hazards models were created incorporating PP as a continuous variable. The interaction of PP with New York Heart Association (NYHA) functional class was examined. Linear and restricted cubic splines were used to study nonlinear association between PP and outcomes. Results: We included 2, 299 patients with a mean(±SD) follow‐up of 3.5 ± 1.8 years. The lowest tertile of PP (≤42 mm Hg) was associated with significantly higher CV mortality and HFH. Cox proportional hazards models showed a reduction in CV death and HFH with higher PP, with adjusted hazard ratios (HR) of 0.91 ( P = 0.02) and 0.93 ( P = 0.04) per 10 mm Hg increase in PP. This relationship was more pronounced in subjects with NYHA functional class III‐IV. Spline analysis showed that the association between PP and CV mortality and HFH was only seen at PP values lower than 40 mm Hg. Conclusions: In patients with advanced HFREF, a low PP (<40 mm Hg) portends a worse prognosis, whereas a high PP (>50 mm Hg) predicts a relatively favourable prognosis.